The Effects of School-Based Handball Intervention on 12–14-Year-Old Children’s Physical Fitness and Performance - Akinci, Yasin; Ateş, Bahar (Physical Education Theory and Methodology, 2023)
Background. School-based physical activity interventions contribute positively to children’s general health, wellness, and quality of life. The present study aims to investigate the effect of a 12-week handball training intervention on the ingredients of physical fitness and physical performances of primary school children. Materials and methods. In this quasi-experimental study, students participating in school-based handball training constitute the intervention group (IG) (n=15, aged 12.3 ± 0.96) and those who do not participate (n=17, aged 12.1 ± 0.83) constitute the comparison group. The linear speed (T30m), change of direction speed (T-test time), lower extremity power (standing long jump (SLJ)), muscular strength and endurance (30-sec curl-ups and push-ups), and estimated maximum oxygen uptake (VO2 max) (YYIRTL-1) were measured at the beginning and end of the handball training session. Independent samples t-test was conducted to test the significant differences in pretests between groups. Paired samples t-test was carried out to analyze statistically significant differences within groups. Results. The results revealed that, except for SLJ test scores, the pre-tests IG performed statistically significantly higher than the CG. In post-test scores, the IG performed statistically significantly higher than the CG in all test scores. In addition, physical fitness performance levels of the IG significantly changed between pre- and post-test (p<0.05) but not in the control group (p>0.05). Conclusions. In conclusion, school-based handball intervention can positively affect students’ physical fitness and performance characteristics.